PENGARUH VARIASI JUMLAH SUDU TERHADAP DAYA LISTRIK YANG DIHASILKAN PADA PROTOTYPE TURBIN PELTON - Mohammad Ulinnuha; Margianto Margianto; Ena Marlina (UNIVERSITAS ISLAM MALANG, 2016)
Water energy can be utilized for generating electricity by exploiting the available potential energy (potential falls and the flow rate). Because energy future is a problem that has always been the concern of every nation, most countries, including Indonesia, the supply of energy is still rely on fossil fuels are limited and thinning, the potential of fossil energy sources in Indonesia and the world are expected to run out within a certain time due to the addition of consumption as well as industrial development increases. Based on data from national energy management 2005-2025 issued by the Ministry of Energy and Mineral Resources (MEMR) in 2005, reserves of oil, gas and coal in Indonesia will be depleted within a certain time. The aim in this research was to determine how many blades are used to determine how much power is generated at the prototype turbine pelton turbine. From these results it appears that the rate of rotation runners are more with the?dominant in the use of blade 20 with the valve opening 90 resulting rotational speed reaches 412 rpm, and generates electric power of 10.66 Watts. while the value of the fluid flow rate (Q) generated as much as 8.4 x 10-4 m/s. the number of blade 18 produces a flow rate of 107.01 m/s.?As for the velocity of fluid flow at the valve opening 90 however generate a fluid flow value of 8.4 x 10-4 m/